ANALYSIS OF THE IMPLEMENTATION OF THE FIFO METHOD AT KITCHEN HOTEL HOLIDAY INN RESORT BARUNA BALI - KOMANG YUDIARTA (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2025)
This study aims to analyze the implementation of the First In First Out (FIFO) method in the management of foodstuffs in the kitchen of Hotel Holiday Inn Resort Baruna Bali. The research method used is qualitative descriptive with data collection techniques through observation, interviews, and documentation. The results of the study show that the application of the FIFO method has been carried out through labeling, rotation, and arrangement of foodstuffs, but the recording of stock in and out has not been optimal. The main obstacles faced are limited human resources and limited operational time, especially during peak hours. The strategy implemented by the management in the form of the preparation of Standard Operating Procedures (SOPs) and daily supervision by outlet leaders is able to increase staff awareness of the importance of FIFO. This study recommends the implementation of a stock recording system, routine training, and periodic evaluation to improve operational efficiency and service quality.